The Mitochondrial T16189C Polymorphism Is Associated with Coronary Artery Disease in Middle European Populations - Mueller, Edith E.; Eder, Waltraud; Ebner, Sabine; Schwaiger, Eva; Santic, Danijela; Kreindl, Tanja; Stanger, Olaf; Paulweber, Bernhard; Iglseder, Bernhard; Oberkofler, Hannes; Maier, Richard; Mayr, Johannes A.; et al. (PloS one, 2011)
The pivotal role of mitochondria in energy production and free radical generation suggests that the mitochondrial genome could have an important influence on the expression of multifactorial age related diseases. Substitution of T to C at nucleotide position 16189 in the hypervariable D-loop of the control region (CR) of mitochondrial DNA (mtDNA) has attracted research interest because of its suspected association with various multifactorial diseases. The aim of the present study was to compare the frequency of this polymorphism in the CR of mtDNA in patients with coronary artery disease (CAD, n = 482) and type 2 diabetes mellitus (T2DM, n = 505) from two study centers, with healthy individuals (n = 1481) of Middle European descent in Austria. CR polymorphisms and the nine major European haplogroups were identified by DNA sequencing and primer extension analysis, respectively. Frequencies and Odds Ratios for the association between cases and controls were calculated. Compared to healthy controls, the prevalence of T16189C was significantly higher in patients with CAD (11.8% vs 21.6%), as well as in patients with T2DM (11.8% vs 19.4%). The association of CAD, but not the one of T2DM, with T16189C remained highly significant after correction for age, sex and body mass index (BMI) and was independent of the two study centers. Our results show for the first time a significant association of T16189C with CAD in a Middle European population. As reported in other studies, in patients with T2DM an association with T16189C in individuals of European decent remains questionable.